Bridging Society 5.0 Skills: The Role of Extracurricular Plan Cards in Enhancing Student Creativity in German Language Education Students at Malang State University - Dewa Ayu Satwikayani; Primardiana Hermilia Wijayati; Oybek Khushbokov (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2026)
This study describes the development of creativity among German Language Education students at Universitas Negeri Malang in the Society 5.0 era through their participation in extracurricular activities planned and documented using Extracurricular Plan Cards (KRE) within the Student Extracurricular Credit System (SKEMA). This study employed a descriptive quantitative approach. Data were collected from 227 students through an online questionnaire distributed via Google Forms and analyzed using descriptive statistics, with results presented in percentages. The findings indicate that students’ creativity development, as reflected in the verified Extracurricular Result Cards (KHE), is predominantly channeled through scientific activities and forums aligned with their discipline, as well as roles as committee members and administrators in student organizations. Students actively engage in collaborative activities and knowledge-building experiences that strongly support their creativity development. High involvement in scientific and organizational activities demonstrates that students are capable of transforming original ideas into tangible and meaningful contributions. These results underscore the importance of self-regulation and active engagement beyond routine documentation to optimally realize creative potential. Students expect the Extracurricular Result Cards system to provide stronger support for competitive pathways in order to stimulate higher-order creative thinking. This study provides practical recommendations for university policymakers, program coordinators, and lecturers to refine the implementation of Extracurricular Plan Cards, thereby better aligning non-formal learning with the creativity demands of the Society 5.0 era.